A Review on Biodegradations of Polymers and its Effect on Environment - Islam, Saiful; Saha, Supriya; Bakr, Abu; Mondal, Ibrahim Hossain (Journal of Composites and Biodegradable Polymers, 2015)
Biodegradation refers to the chemical dissolution of materials by microorganisms or other biological means. Biodegradability of a material refers to the ability of that material to be decomposed by biological agents, especially bacteria. Carbon dioxide and water are produced during aerobic biodegradation and carbon-dioxide, water and methane are produced during anaerobic biodegradation. The process of degradation induces changes in polymer properties resulting in bond scission, chemical transformation and formation of new functional groups. Most of the polymers are non-degradable and some are degraded after longtime and causes environmental pollution. Biodegradation of polymers have both positive and negative impact on environment but the negative impacts are more remarkable. Because some polymeric materials take about million year to degrade in environment. Disposal problem will be introduced from these materials and finally destroy our ecological balance. To protect the environment some advisory steps should be taken such as development of standards and testing, life cycle assessment, determination of appropriate disposal environments. Environmental benefits that may be derived from the use of biodegradable polymers.